Geopolitics of The Initiative for The Integration of The Regional Infrastructure of South America - Giudice Baca, Victor (2022)
The IIRSA Project was born in Brasil year 2000. The strategic goal of IIRSA is to build a road and ports system able to conquer and ocuppy,   The  Amazonic and tranandinean spaces orderly. The IIRSA Project is composed of  ten  Axis. The Interoceanic Axis that unites the ports of Santos (Brazil) and Ilo (Peru) is the main objet of analysis of this paper. The largest interest of Brasil, Mercosur and  Bolivia is  to  buil trade ports leading them to the pacific ocean across Peruvian and Chile territories. The IIRSA  Project  involves 12  countries of  South  America.